The Impact of COVID-19 Lockdown on Service Utilization Among Chronic Disease Patients in South Africa - Micheal Kofi Boachie; Mariana Khoza; Susan Goldstein; Maggie Munsamy; Karen Hofman; Evelyn Thsehla (SAGE Publishing, 2023)
Introduction: Globally, the COVID-19 pandemic has brought many disruptions in health service delivery. Evidence show that the pandemic has negatively affected routine healthcare utilization such as maternal and child health services, but the literature on the effect on non-communicable diseases (NCDs) is scant in South Africa. These disruptions can have long-term health and economic implications for patients. Objective: To estimate the impact of COVID-19 lockdown on service utilization among chronic disease patients in South Africa using administrative data. Methods: Using monthly data from the Centralized Chronic Medication Dispensing and Distribution (CCMDD) program database covering November 2018 to October 2021, we examined the effects of COVID-19 lockdown on utilization among patients receiving antiretroviral therapy (ART) medication only (ART-only), patients receiving both ART and NCD medication (ART + NCD), and patients receiving NCD medications only (NCD-only). We employed segmented interrupted time series approach to examine the changes. We stratified the analysis by socioeconomic status. Results: We found that, overall, the lockdown was associated with increased utilization of CCMDD services by 10.8% (95% CI: 3.3%-19%) for ART-only and 10.3% (95% CI: 3.3%-17.7%) for NCD-only patients. The increase in utilization was not different across socioeconomic groups. For patients receiving ART + NCD medications, utilization declined by 56.6% (95% CI: 47.6%-64.1%), and higher reductions occurred in low SES districts. Conclusion: Patients should be educated about the need to continue with utilization of disease programs during a pandemic and beyond. More efforts are needed to improve service use among patients with multi-morbidities.